148-164 Washington Street, ca. 1858-60 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking southwest down the left side of a cobblestoned Washington Street between Milk and Franklin Streets. Many buildings have business signage affixed to them. Further down the street awning provide shade for the street level shops. 12 x 9 1/2 Photographs